Anesthesia-induced Suppression of Human Dorsal Anterior Insula Responsivity at Loss of Volitional Behavioral Response. (April 2016) - Warnaby, Catherine Elizabeth; Seretny, Marta; Ní Mhuircheartaigh, Roísín; Rogers, Richard; Jbabdi, Saad; Sleigh, Jamie; Tracey, Irene
Abstract : Background: It has been postulated that a small cortical region could be responsible for the loss of behavioral responsiveness (LOBR) during general anesthesia. The authors hypothesize that any brain region demonstrating reduced activation to multisensory external stimuli around LOBR represents a key cortical gate underlying this transition. Furthermore, the authors hypothesize that this localized suppression is associated with breakdown in frontoparietal communication. Methods: During both simultaneous electroencephalography and functional magnetic resonance imaging (FMRI) and electroencephalography data acquisition, 15 healthy volunteers experienced an ultraslow induction with propofol anesthesia while a paradigm of multisensory stimulation ( i.e., auditory tones, words, and noxious pain stimuli) was presented. The authors performed separate analyses to identify changes in (1) stimulus-evoked activity, (2) functional connectivity, and (3) frontoparietal synchrony associated with LOBR. Results: By using an FMRI conjunction analysis, the authors demonstrated that stimulus-evoked activity was suppressed in the right dorsal anterior insula cortex (dAIC) to all sensory modalities around LOBR. Furthermore, the authors found that the dAIC had reduced functional connectivity with the frontoparietal regions, specifically the dorsolateral prefrontal cortex and inferior parietal lobule, after LOBR. Finally, reductions in the electroencephalography power synchrony between electrodes located in these frontoparietal regions were observed in the same subjects after LOBR. Conclusions: The authors conclude that the dAIC is a potential cortical gate responsible for LOBR. Suppression of dAIC activity around LOBR was associated with disruption in the frontoparietal networks that was measurable using both electroencephalography synchrony and FMRI connectivity analyses. Abstract : Simultaneous electroencephalography and functional magnetic resonance imaging in 15 healthy volunteers undergoing ultraslow induction of propofol anesthesia identified suppression of stimulus-evoked activity in the right dorsal anterior insula cortex coincident with reduced functional connectivity with frontoparietal regions at loss of responsiveness. The dorsal anterior insula cortex is a potential cortical gate underlying loss of responsiveness that might mediate subsequent loss of functional connectivity and information integration at deeper levels of anesthesia.